TASHKENT STATE DENTAL INSTITUTE COMPARATIVE ANALYSIS OF INTRAORAL SCANNERS - Amanullaev , R.A.; Manukyan , A.O. (Educational Research in Universal Sciences, 2023)
The evolution of intraoral scanners (IOSs) is rapid, and new IOSs appear on the market with different properties depending on the manufacturers. There is no uniform rating system based on a defined set of aspects that has reported in the literature that can be used to compare these devices. This validation study aimed to compare different IOSs based on objective and comprehensive parameters.